Problems and Prospects of Digitalisation in the Field of Jurisprudence to Ensure Cyber Protection of Information - Balliu, Henris; Xhixho, Erisa; Abdukarimova, Nazira; Adylova, Nazgul; Abbasov, Nail (Law, State and Telecommunications Review, 2025)
[Purpose] The purpose of the study is to examine the impact of digitalisation on the field of jurisprudence with a special focus on ensuring cyber protection of information. [Methodology/approach/design] The study methodology includes the analysis of cyber threats for law firms, such as phishing and distributed denial of service (DDoS) attacks, an assessment of international cybersecurity standards (Budapest Convention, ISO/IEC 27001), and the use of modern security technologies (encryption, multi-factor authentication). [Findings] Employee training programmes and the possibilities of using artificial intelligence and machine learning to automate data protection were examined. Electronic platforms simplify the exchange of documents and increase the transparency of interactions due to the session recording function. The legal field is facing acute cybersecurity problems due to the processing of confidential information. The main types of cyber-attacks faced by law firms include phishing, ransomware, and DDoS attacks. Each of these attacks can have serious consequences for data security, the reputation of companies, and their ability to provide legal services. [Practical implications] The research underscores the critical need for law firms to implement robust cybersecurity measures, including compliance with international standards and regular employee training, to protect sensitive information and maintain client trust. This shift not only enhances operational efficiency and compliance but also positions firms competitively in a digitally-driven market, ultimately impacting client access to legal services and the overall landscape of legal practice. [Originality/value] The development of specialised software for the legal field has opened up new opportunities to improve the efficiency and protection of information, ensuring compliance with legislation and integration with external systems.